Spatial-temporal patterns of homicide in socioeconomically deprived settings: violence in Alagoas, Brazil, 2006‒2015 - Kevan Guilherme Nóbrega Barbosa; Blake Byron Walker; Alessandra Vieira da Silva; Gessyca Luyze Procópio Gonzaga; Evanisa Helena Maio de Brum; Mara Cristina Ribeiro (Taylor & Francis Group, 2021)
Background Homicide presents a significant health burden globally, but geographical differences in homicide rates necessitate focussed analyses of spatial and temporal patterns, particularly in affected areas. The highest rates are concentrated in regions in Central and South America, but analyses of sub-regional patterns and sex-specific differences may yield important information for addressing the upstream causes of homicide at the community level. Objective This study examines and presents spatial and temporal patterns of homicide victims from 2006 to 2015 in the state of Alagoas, Brazil, focussing on the municipality scale and differentiated by victims' sex. Methods Data comprising victims' age, sex, the date, time, and the municipality of the homicide incident were acquired from the Brazilian National Mortality Information System. These data were aggregated by municipality, and we made quantitative comparisons of sex-specific homicide rates between the capital city of Macieó metropolitan region and the peripheral, predominantly rural regions. Empirical Local Bayes methods were used to adjust per-capita homicide risk estimates and map the results. Results A total of 19,560 homicides occurred during the study period, with an average of 60.4 per 100,000 inhabitants; the metropolitan region rate was 81.8, compared to 46.5 for the remaining regions. The male homicide rate was 115.9 per 100,000, compared to 7.1 for females. Empirical Local Bayes mapping showed strong clustering of male homicide risk in specific cities near the capital, while female risk was more dispersed throughout the region. Conclusions The risk of male victim homicide observed for the metropolitan region of Alagoas was amongst the highest globally, particularly during the period 2012-2014. Geographical differences in male and female risk may indicate differences in risk factors and highlight a need for prevention programmes that take into account gender-specific pathways of violence.